2016
DOI: 10.14503/thij-15-5505
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Mycotic Thoracoabdominal Aortic Aneurysm Involving the Celiac Artery

Abstract: A mycotic aortic aneurysm (AA) is a rare and dangerous condition that is associated with substantial morbidity and mortality rates. It is defined as an aortic aneurysm with one or more of the following clinical signs: fever, elevated white blood cell count, positive blood or aneurysmal wall cultures, or purulent operative findings. Of all aortic aneurysms, 0.8% to 3.4% are mycotic.1 Those mycotic AAs that involve visceral arteries can result in disastrous sequelae, such as gangrene of the intestine. Here we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Although a few case reports showed good outcomes with the endovascular approach associated with antibiotic therapy, lifelong antibiotherapy is advisable as well as close monitoring, strict analytic follow-up, and repeated imaging to detect additional aneurysm formation because of theoretical concerns for recurrent infection or progression. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Although a few case reports showed good outcomes with the endovascular approach associated with antibiotic therapy, lifelong antibiotherapy is advisable as well as close monitoring, strict analytic follow-up, and repeated imaging to detect additional aneurysm formation because of theoretical concerns for recurrent infection or progression. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative culture was positive for Streptococcus pneumoniae. After more than 17 months from repair, the patient was alive and free from infection [94].…”
Section: Literature Reviewmentioning
confidence: 93%
“…For these reasons, over the years, many authors have reported a plethora of alternative, less invasive, hybrid, or endovascular approach. Here, several cases of infectious aneurysms involving visceral branches are reported, with particular attention to treatment strategies and relative results [80,81,[87][88][89][90][91][92][93][94].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several [4][5][6][7]. Medical treatment alone is not sufficient to treat infected aneurysm due to rapid progression of pseudoaneurysm; surgical treatment is warranted to avoid aortic fistula, aneurysm rupture and bleeding [8,9]. We report a first case of mycotic aneurysm without endocarditis due to Streptococcus constellatus in 58 years old male with diffuse large B cell lymphoma from East Sussex Healthcare Trust (ESHT), United Kingdom.…”
Section: Introductionmentioning
confidence: 99%